Analisis Perbandingan Skema Pembayaran Digital Dengan Metode Paylater Pada Ecommerce Di Indonesia - ROSALIKA, IKA (LPPM Universitas Bina Sarana Informatika, 2025)
Abstracts - The development of information technology plays an important role in the world of digital transactions. The emergence of digital payment systems with various features and conveniences on offer has become one of the attractions in today's society. One of them is the payment method with paylater. This method is known as buy now pay later. This method is often found when shopping online on various e-commerce platforms by providing very large discounts and easy installments. However, apart from that, the risk that occurs when using the pay later method is that failure to pay at a certain maturity date results in very high fines and interest. This causes bad credit. Therefore, it is necessary to have a special understanding regarding the calculation of payments or installments when using the paylater method so that people are wise in managing their finances and do not get caught up in bad credit.Keywords: Digital Transactions; Ecommerce Platforms; Online Credit